Intensitas Serangan Hama Spodoptera frugiperda dan Keanekaragaman Musuh Alaminya pada Sentra Pertanaman Jagung di Kabupaten Banyumas Provinsi Jawa Tengah - Endang Warih Minarni; Mutala'liah Mutala'liah; Nurtiati Nurtiati (RADIKULA: Jurnal Ilmu Pertanian, 2026)
Spodoptera frugiperda has become a major pest of maize in Banyumas Regency. This study aimed to determine the population, infestation intensity, and diversity of indigenous natural enemies associated with S. frugiperda. Sampling was conducted using a purposive random sampling method across five maize-producing districts; within each district, five villages were selected, five plots were chosen per village, and 10 plants per plot were sampled using a diagonal pattern. The results showed that S. frugiperda exhibited a regular distribution pattern, with populations ranging from 0.24 to 1.26 larvae per plant and infestation intensities between 0.34% and 62.2%. The highest population levels and infestation intensities were observed in Banjarsari Wetan and Datar villages, Sumbang District. Fourteen species of natural enemies were identified, including spiders, predatory insects, parasitoids Apanteles sp. and Charops sp.), and the entomopathogenic fungi Fusarium oxysporum and Aspergillus oryzae. No single natural enemy species was found to be dominant. For locations where pest populations exceeded the economic threshold, the use of systemic insecticides combined with the rotation of active ingredients is recommended